Trophic Status of the Boko-Boko Peat Swamp in the Langgam Village, Langgam District, Pelalawan Regency, Riau - Sihaloho, Maria Virgita; Siagian, Madju; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The area around the Boko-Boko peat swamp has been used for palm plantation. Remains of fertilizer and pestiside used in the plantation may enter the water and decrease the water quality of the swamp. To understand the trophic status of the Boko-Boko peat swamp’s waters, a research was conducted in March 2016. There were three sampling stations namely Station 1, Station 2, and Station 3 and in each station there were three sampling points, in the surface, 1.5 secchi and in the bottom. Samplings were conducted 3 times, once/week. Trophic status was calculated based on Carlson’s Trophic State Index (TSI). Results shown that the transparency was 49 – 60 m, total phosphorus 0.13 – 0.17 mg/L, chlorophyll-a 3.12 – 6.19 μg/L, depth 45 – 250 cm, temperature 30 - 31ºC, pH 4 – 5, dissolved oxygen 0.41 – 3.26 mg/L, free carbondioxide 7.33 – 21.31 mg/L and nitrate 0.44 – 0.72 mg/L. Based on Carlson’s TSI, the water of the Boko-Boko peat swamp is categorized as moderate-eutrophic.Keywords : Peat Swamp, Boko-Boko swamp, Trophic Status, Trophic State Index